Parenting styles in white‐rumped swallows (Tachycineta leucorrhoa) show a trade‐off between nest defense and chick feeding. (21st June 2018) - Wischhoff, Uschi; Marques‐Santos, Fernando; Manica, Lilian T.; Roper, James J.; Rodrigues, Marcos
Abstract: Studies about personalities in wild animals usually focus on five categories of behavioral traits that do not easily accommodate all aspects of parental care, a class of behaviors with direct consequence to reproductive success. Parental care can vary consistently between individuals and constitute parenting styles. Here we investigate the consistency of four behaviors of parental care across two breeding seasons of white‐rumped swallows Tachycineta leucorrhoa in southern Brazil. These behaviors are a prospection of potential nest‐sites, nest defense against predators or conspecifics, and chick feeding. If these first three behaviors are consistent, they can be classified according to the standard categories of personality as exploration, boldness, and aggressiveness, respectively. We find that all behaviors, except exploration, are consistent between individuals in the long term. We also show that, besides individual identity, couple identity is an important component explaining variation in behavior. This pattern can arise if behavior influences pair formation or if behavior is a consequence of a common environment affecting the couple. We show that, depending on the parental task, males or females are more consistent, suggesting that sexes are adopting different strategies of parental care allocation. We then investigate if there is a trade‐off between nest defense and chick feeding. We find that birds that defend more also feed the brood less often and suggest that testosterone might be the mechanism modulating this trade‐off. Lastly, we discuss the implications of our results to mate choice and highlight the need for studies linking parenting styles to fitness in swallow species.